East Asia Today - Azevedo, Fátima (2020)
East Asia attracts growing interest in the West. Th e region is the world’s hotbed of economic growth, led by burgeoning China aided by more advanced Asian economies investing heavily in manufacturing and trading networks involving China. Western entrepreneurs clamor to join the China wave.